Fundamentals of entrepreneurship (ENT 300) : Puffy Fluffy pastries / Angeli Shima Eli … [et al.] - Eli, Angeli Shima; Ujang, Celine; Jonathan, Escardina Grace; Do Anyi, Kathryn; Bollhassan, Nurul Ainul Assyakirin (2019)
Business Opportunity is defined as a situation that enable an Entrepreneur to offer marketable for both products and also services to interested buyers or a user. Hence, an opportunity is to generate income as a Business and not employment opportunity. This report is intended to present a Business Opportunity on Puffy Fluffy Pastries Hence, we have touched all areas of business Opportunity that have been list or written down in this report. Besides, there is five or ten pastry that were be made in this business for our grand opening business. This business been chosen because patisserie were rarely has been seen at Kota Samarahan area especially.